Urethane anesthesia depresses activities of thalamocortical neurons and alters its response to nociception in terms of dual firing modes - Huh, Yeowool; Cho, Jeiwon (Frontiers in Behavioral Neuroscience, 2013)
Anesthetics are often used to characterize the activity of single neurons in-vivo for its advantages such as reduced noise level and convenience in noxious stimulations. Of the anesthetics, urethane had been widely used in some thalamic studies under the assumption that sensory signals are still relayed to the thalamus under urethane anesthesia and that thalamic response would therefore reflect the response of the awake state. We tested whether this assumption stands by comparing thalamic activity in terms of tonic and burst firing modes during ‘the awake state’ or under ‘urethane anesthesia’ utilizing the extracellular single unit recording technique. First we have tested how thalamic relay neurons respond to the introduction of urethane and then tested how urethane influences thalamic discharges under formalin-induced nociception. Urethane significantly depressed overall firing rates of thalamic relay neurons, which was sustained despite the delayed increase of burst activity over the 4 hour recording period. Thalamic response to nociception under anesthesia was also similar overall except for the slight and transient increase of burst activity. Overall, results demonstrated that urethane suppresses the activity of thalamic relay neurons and that, despite the slight fluctuation of burst firing, formalin-induced nociception cannot significantly change the firing pattern of thalamic relay neurons that was caused by urethane.